Nano-structured super-capacitor electrodes - Quah, Edwin Yi Han. (2012)
A nano-composite comprises of sphere-like MnO2 nanocrystals supported by reduced graphene oxide (rGO) sheets by has been synthesized through a simple chemical route in water. The nano-sized MnO2 were homogeneously distributed on go sheet, which have been confirmed by images from scanning electron microscopy (SEM) analysis depicting its surface morphology. Fourier transform infrared spectroscopy (FTIR) was used to determine the respective functional groups, x-ray diffraction (XRD) was used to determine the phases present within the composite and thermal gravimetric analysis (TGA) was used to determine the moisture, volatile contents and degradation temperatures of each composite.